A preliminary study on the social and emotional experience of parents of children with cleft lip and palate - Teoh, Hsien-Jin *; Woo, Pei Jun *; Cheong, Sau Kuan *; Neo, Ee Lynn * (Sunway University College, 2008)
There are very few studies that describe the emotional and social experiences of parents of children with cleft lip and?or palate who are undergoing treatment. To understand these circumstances, 34 parents of children with cleft lip and?or palate were surveyed to find out about the parents? social and emotional experiences of having children with this physical disorder. The research was carried out using structured questionnaires that parents completed during a support group meeting. The questionnaires included questions on the reactions of people toward the child, parents? emotional reactions, social support, coping strategies and resources used. Results of the study indicated that parents do need some assistance during the early stages of treatment. Furthermore, pediatricians play a very important role in the follow-up of treatment, empowerment of parents, and dissemination of information on the child?s condition. Contrary to much speculation, the parents reported that they are generally not stigmatized, and took a proactive approach towards finding out information about the disorder, and also about caring for their children. The study concluded by indicating that future studies would need to have larger samples, span a wider age groups, focus on the children?s first 12 months, and also their experiences when they begin to attend school.